Evaluating the Effectiveness of Trade Conditions in Fund-Supported Programs. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Approximately half of the countries that had IMF-supported programs during 1993-2003 also had trade-related conditions. A large literature has shown that trade openness is an essential part of the environment in which economic growth and poverty reduction take place.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: United Arab Emirates